Hybridization Technique in Tartary Buckwheat (Fagopyrum tataricum Gaertn) (Nepal Agriculture Research Journal, 2014)
N/ANepal Agric. Res. J. Vol. 9, 2009, pp. 118-128DOI: http://dx.doi.org/10.3126/narj.v9i0.11650